The ethical values based on maqasid syariah for enhancing self identity among students - Siti Aishah, Maliki; Rahimah, Embong; Berhanundin, Abdullah (2015)
Students are the main assets for any race and nation. This is why they should be equipped with knowledge and skills since their childhood which are beneficial for their future. However, they are facing various problems and difficulties when dealing with their emotional pressures. Consequently, this will affect the quality of their learning process and finally, will deteriorate their achievement and performance in all aspects. The solution for this problem is difficult to be achieved unless the students have a strong self-identity. Hence, moral education plays a crucial role in developing the self-identity among students. Moral education is a very important subject matter to help in solving moral problems and enhancing self-esteem and self-identity. But to which extent the students are aware of and practice what they have learned in the subject of moral education in their schools. They should not study the subject for sake of getting good result in their examination, but also for shaping good attitudes, behaviours in their daily lives? The proper ethical values should be infused into moral education at all level of schooling including higher education. The infusion of ethical values should be done formally or informally by those are responsible to educate individuals since they were born. The ethical values derived from the most authentic source of values will be contributing to enhancing students’ self-identity. Therefore, the study suggests for deriving all ethical values and principles from the essentials (Dharuriyyat) of the objectives of Islamic Law (Maqasid Syariah) which are the preservation of five matters namely religion, soul, property, progeny and intellect. This study gives some implications on the content of moral education which should be modified accordingly. Moral education should emphasize all aspects of students development including emotional, moral, cognitive and social, in order to develop their self-identity holistically.